Peningkatan Produksi Kompos Melalui Komposter Anaerob dan Manajemen Keuangan untuk Pengolahan Sampah Pangan Berkelanjutan - Putri Manurung, Nancy Eka; Africano, Fernando; Wardhani, Dyah Utari Yusa; Nurfathiyyah, Kayla Alifah; Irianti, Imelsya (JPM: Jurnal Pengabdian Masyarakat, 2025)
The Community Service Program (PKM) aims to empower Qur’anic Farm Indonesia through an innovative approach to converting food waste into compost, emphasizing social and environmental values. This program was designed to address two main challenges: slow compost production due to reliance on conventional aerobic methods, which take up to three months, and the absence of a proper financial recording system for profitability analysis. Technological solutions were introduced through the implementation of waste shredding machines and anaerobic digesters as Appropriate Technology (TTG), which reduce raw material size and significantly shorten decomposition time. On the management side, financial training focused on preparing transparent and easily understandable simple reports. The program was carried out through systematic stages using discussion and Participatory Action Research (PAR) methods, includin: field surveys, preparation, socialization, training, implementation of TTG, mentoring, evaluation, and sustainability strategies. Key outcomes included increased participant knowledge about anaerobic composting, enhanced compost production capacity through higher harvesting frequency, and the establishment of a basic accounting system to support financial decision-making. The long-term impacts encompass the creation of a sustainable enterprise both economically through increased profits and socially through contributions to orphan education and local food waste reduction. This program not only boosts production efficiency but also builds a foundation for healthy and independent business governance.